Titanium vanadium nickel, TiV0.08Ni0.92 - Huizi Liu; Changzeng Fan; Bin Wen; Lifeng Zhang (IUCrData)
A single-crystal of the intermetallic phase TiV0.08Ni0.92 was obtained by the high-temperature sintering of a mixture of nominal composition Ti0.9V0.1Ni. The title compound adopts the CsCl structure type with one site solely occupied by Ti and the other by V and Ni with a ratio of 0.08 (7):0.92 (7).